Financial Tables Reports Gaps in Jordanian Islamic Banks - Nazal, Abdullah Ibrahim (The Economics and Finance Letters, 2017)
This study is one of very few studies which have investigated financial table’s reports gaps in Jordanian Islamic banks. There must be way to face ten gaps by unit efforts between Supervisory Sharia Board report, External Auditor report and Islamic Managing Announcing Disclosure. There work must be unit as integration to give one result. Jordanian Islamic banks case study shows this cooperation to get fair result for major accounting data in financial tables. The searcher recommended to apply model as work paper to study strength or weakness of gaps which impact the financial analysis success in Islamic banks.